Protection of workers' personal data: General principles - Frank Hendrickx (International Labour Organization (ILO), 2022)
This working paper gives an overview of legal standards related to personal data protection. It explores trends, principles and good practices and brings them in relation to the world of work. The aim of this working paper is to give a global and updated outlook of the leading and basic legal principles and standards in this area. The focus is on data protection principles which have a general nature and which can be embedded in a global approach. This working paper attempts to expose and clarify general data protection principles, having in mind that these principles are applicable in the context of the evolving employment relationship, taking into account technological evolutions. An understanding of general data protection principles is considered necessary to comprehend their application in the work environment and to build further towards principles that relate to more specific areas and problem fields.
Keywords: 330; workers; working conditions; COVID-19